2016
DOI: 10.2147/ijn.s110146
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine engulfed by macrophages for targeted tumor therapy

Abstract: Macrophages, exhibiting high intrinsic accumulation and infiltration into tumor tissues, are a novel drug vehicle for directional drug delivery. However, the low drug-loading (DL) capacity and the drug cytotoxicity to the cell vehicle have limited the application of macrophages in tumor therapy. In this study, different drugs involving small molecular and nanoparticle drugs were loaded into intrinsic macrophages to find a better way to overcome these limitations. Their DL capacity and cytotoxicity to the macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…and chemokines (e.g., CCL-5, 7, 8, 12, etc. ), [46] and navigate to the diseased sites, passing multiple biological barriers along the way. This holds true for central tumor areas, which are often avascular and inaccessible to conventional therapeutics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and chemokines (e.g., CCL-5, 7, 8, 12, etc. ), [46] and navigate to the diseased sites, passing multiple biological barriers along the way. This holds true for central tumor areas, which are often avascular and inaccessible to conventional therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…injected macrophages to migrate to inflamed tissues. [6,24] We reason that if drug-loaded nanoparticles do not release the payloads in the early hours of cell entry, the adverse impacts can be held in check in spite of a high apparent drug content. This would buy time for macrophages to traffic to tumors, and release therapeutics in situ to induce efficient and selective cancer cell killing (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Controlled anticancer drug release [108,137] Tumor targeted therapy [138][139][140] Biomedical optical imaging [141] N-octyl-N-trimethyl chitosan Self-assembled polymeric micelles…”
Section: Cs/derivativesmentioning
confidence: 99%
“…Among the endogenous cells, macrophages have been reported as a tumor-targeted transport vector and attracted extensive research attention due to their strong phagocytic capacity and tolerance to chemotherapeutic drugs [6, 7]. Some studies have confirmed the feasibility of using macrophages to transport chemotherapeutic drugs or drug-loaded nanoparticles to the tumor site [811]. However, the low drug-loading capacity and insufficient drug release at the tumor site have limited the use of macrophages as a tumor targeting vector [12].…”
Section: Introductionmentioning
confidence: 99%